Transcriptional comparison of adult human primary Retinal Pigment Epithelium, human pluripotent stem cell-derived Retinal Pigment Epithelium, and ARPE19 cells - Markert, Elke K.; Klein, Holger; Viollet, Coralie; Rust, Werner; Strobel, Benjamin; Kauschke, Stefan G.; Makovoz, Bar; Neubauer, Heike; Bakker, Remko A.; Blenkinsop, Timothy A. (Frontiers in Cell and Developmental Biology, 2022)
The therapeutic potential of pluripotent stem cells is great as they promise to usher in a new era of medicine where cells or organs may be prescribed to replace dysfunctional tissue. At the forefront of are efforts in the eye to develop this technology as it lends itself to in vivo monitoring and sophisticated imaging modalities. In the retina, retinal pigment epithelium (RPE) is the most promising replacement cell as it is a single layer, relatively simple to transplant and associated with dozens of eye diseases. However, after transplantation, they may transform and lead to complications. This transformation may be partially due to an incomplete maturation. With the goal of learning how to mature RPE, we compared iPSC-RPE with adult primary RPE and the immortalized ARPE-19 line. We cultured ARPE-19, iPSC-RPE and adult human RPE for 1 month, evaluating morphology, RPE marker staining and transepithelial electrical resistance as quality control indicators. We then isolated RNA for bulk RNA-sequencing and DNA for genotyping. We genotyped adult RPE lines for the top Age-related Macular Degeneration (AMD) and Proliferative Vitreoretinopathy (PVR) risk allele polymorphisms. Transcriptome data verified that both adult and iPSC-RPE exhibit similar RPE gene expression signatures, significantly above ARPE-19. In addition, in iPSC-RPE, gene networks relating to epithelial to mesenchymal transition (EMT), stem cell maintenance, retina development, and muscle contraction were significantly elevated above adult RPE. We compared adult human RPE to iPSC-RPE in a model of EMT and observed an increased sensitivity of iPSC-RPE to producing contractile aggregates in vitro which resembles incident reports upon transplantation. P38 inhibition was capable of inhibiting iPSC-RPE derived aggregates. In summary, we find the epigenetic signature of iPSC-RPE conveys an immature RPE state which may be ameliorated by targeting “immature” gene regulatory networks.